Bentuk Sarkasme dalam Media Sosial Tik Tok - Sari, Irma; Rahim, Abdul Rahman; Paida, Andi (Universitas Muhammadiyah Sorong, 2023)
This article or article aims to describe the form of using sarcasm in social media Tik Tok. The problem is focused on the form of using sarcasm on social media Tik Tok. In order to approach this problem, Gorys Keraf's theoretical references are used regarding language style, sarcasm and its form and function. The data were collected through documentation and note-taking techniques and then analyzed qualitatively. This study concludes that the results of the study show that there are 50 data on the use of sarcasm language which are categorized into trait sarcasm, action sarcasm, action result sarcasm, appeal sarcasm and designation sarcasm. The use of sarcasm language found is words in groups of words that have aggressive meanings, are satirical, contain ridicule, and the use of titles or titles for people without maximizing respect let alone demeaning and insulting the interlocutor is a characteristic of the opinions left by netizens on the platform Tik Tok social media.